Case report: Metagenomic next-generation sequencing for the diagnosis of rare Nocardia aobensis infection in a patient with immune thrombocytopenia - Liang, Xiaocui; Liu, Xiaoyu; Huang, Zhimin; Qiu, Fei; Jiang, Yini; Li, Chunhong; Deng, Zhenfeng; Wu, Jinyu (Frontiers in Medicine, 2024)
Background Nocardiosis poses a diagnostic challenge due to its rarity in clinical practice, non-specific clinical symptoms and imaging features, and the limitations of traditional detection methods. Nocardia aobensis (N. aobensis) is rarely detected in clinical samples. Metagenomic next-generation sequencing (mNGS) offers significant advantages over traditional methods for rapid and accurate diagnosis of infectious diseases, especially for rare pathogens. Case presentation A 52-year-old woman with a history of immune thrombocytopenia for over 2 years was hospitalized for recurrent fever and cough lasting for 10 days. Her initial diagnosis on admission was community-acquired pneumonia, based on chest computed tomography findings of lung inflammation lesion. Empirical treatment with moxifloxacin and trimethoprim-sulfamethoxazole (TMP-SMZ) was initiated. However, her condition failed to improve significantly even after 1 week of treatment. Bronchoalveolar lavage fluid (BALF) subjected to mNGS revealed the presence of N. aobensis, resulting in a diagnosis of pulmonary nocardiosis caused by N. aobensis. This diagnosis was also supported by Sanger sequencing of the BALF. After adjusting the antibiotic regimen to include TMP-SMZ in combination with imipenem, the patient’s condition significantly improved. She was finally discharged with instructions to continue oral treatment with TMP-SMZ and linezolid for 6 months. The patient’s first follow-up 1 month after discharge showed good treatment outcomes but with obvious side effects of the drugs. Consequently, the antibiotic regimen was changed to doxycycline, and the patient continued to improve. Conclusion We report the first detailed case of pulmonary nocardiosis caused by N. aobensis diagnosed by mNGS. mNGS could be an effective method that facilitates early diagnosis and timely decision-making for the treatment of nocardiosis, especially in cases that involve rare pathogens.